Penyuluhan Gizi Seimbang Pada Orang Tua Balita Melalui Media Barcode Interaktif Di Wilayah Kerja Posyandu Mekarsari: Penyuluhan Gizi Seimbang Pada Orang Tua Balita Melalui Media Barcode Interaktif Di Wilayah Kerja Posyandu Mekarsari - Anggraeni, Priska Nandya; Ethicawati, Sulfi; Widyastuti, Anggraeni; Riyana, Oktrida; Alfiyanti, Dera (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2025)
Toddlers are an age group vulnerable to nutritional problems due to an underdeveloped immune system, making them in need of a balanced nutritional intake to support growth and development. A lack of parental knowledge particularly among mothers—regarding the principles of balanced nutrition is one of the contributing factors to the high prevalence of malnutrition and stunting in toddlers, including in RW 11, Palebon Subdistrict, Pedurungan District. The aim of this activity was to improve parents’ knowledge and understanding of the importance of balanced nutrition through health education using interactive barcode-based media. The methods used included face-to-face counseling, nutritional status assessments at the local Posyandu (integrated health post), and the provision of digital educational materials accessible via QR Code. Evaluation was carried out through Q&A sessions and assessments of participants’ understanding before and after the counseling. The results showed a significant increase in parents’ knowledge of the concept of balanced nutrition, sources of nutritious food, and how to meet children's nutritional needs. Parents were able to explain the material presented and demonstrated a change in attitude when choosing healthy food for their toddlers. In conclusion, nutrition counseling using interactive barcode media proved effective in increasing parents’ knowledge and attitudes, and can serve as an innovative alternative for preventing nutritional problems such as stunting in the community.